The Triple System for Regulating Women's Reproduction. Issue 2 (2015) - Carbone, June; Cahn, Naomi
Abstract : A half century ago, American family lives did not differ markedly by class or region; children were born to married parents, shotgun marriages helped keep the nonmarital birth rate low, and women stayed home unless economics forced them into the workplace. In that era, the Utah Supreme Court cited New York cases in addressing non-marital cohabitation and family reforms that started in California swept much of the country in short order. While we know that our halcyon memories of those years cloak substantial conflict, we did sweep much of it under the rug; politicians, judges, religious leaders, and even family sit-coms in those years expressed remarkable agreement about family aspirations.